Rapsyn mutations in hereditary myasthenia: distinct early- and late-onset phenotypes. - Burke, G; Cossins, J; Maxwell, S; Owens, G; Vincent, A; Robb, S; Nicolle, M; Hilton-Jones, D; Newsom-Davis, J; Palace, J; Beeson, D (2003)
Rapsyn mutations in 16 unrelated patients with a congenital/hereditary myasthenic syndrome were identified, and a mutation (N88K) common to each of them was found. Two distinct phenotypes were noted: early and late onset. The former is frequently associated with arthrogryposis multiplex congenita and life-threatening crises. The late-onset phenotype developed in adolescence or adulthood and was initially mistaken for seronegative myasthenia gravis. Recognition of this late-onset phenotype should prevent inappropriate immunotherapy.